In-situ calcite U-Pb geochronology of hydrothermal veins in Thailand: New constraints on Indosinian and Cenozoic deformation. (February 2021) - Simpson, Alexander; Glorie, Stijn; Morley, Chris K.; Roberts, Nick M.W; Gillespie, Jack; Lee, Jack K.
Highlights: First calcite U-Pb geochronlogy on tectonic veins in Thailand. Timing of calcite precipitation is constrained to Indosinian II and Cenozoic. Redox-sensitive element maps are used to decipher U-Pb data. Abstract: U-Pb dating of calcite veins allows direct dating of brittle deformation events. Here, we apply this method to hydrothermal calcite veins in a fold-and-thrust belt and a large scale strike-slip fault zone in central and western Thailand, in an attempt to shed new light on the regional upper crustal deformation history. Calcite U-Pb dates for the Khao Khwang Fold and Thrust Belt (KKFTB) of 221 ± 7 Ma and 216 ± 3 Ma demonstrate that calcite precipitated during tectonic activity associated with stage II of the Indosinian Orogeny (Late Triassic – Early Jurassic). One additional sample from the KKFTB suggests that the Indosinian calcite has locally been overprinted by a Cenozoic fluid event with a different chemistry. For the Three Pagodas Fault Zone (TPFZ), our calcite U-Pb results suggest a complex, protracted history of Cenozoic brittle deformation. Petrographic information combined with contrasting redox-sensitive trace elemental signatures suggest that the vein arrays in the TPFZ precipitated during two distinct events of brittle deformation at 48 and 23 Ma. These dates are interpreted in the context of far-field brittle deformation related to the India-Eurasia collision. The presented calcite U-Pb dates are in excellent agreement with published age constraints on the deformation history of Thailand, demonstrating the utility of the method to decipher complex brittle deformation histories. The paper further illustrates some of the complexities in relation to calcite U-Pb dating and provides suggestions for untangling complex datasets that could be applied to future studies on the deformation history of Thailand and other regions.